2011
DOI: 10.4314/njbas.v19i1.69360
|View full text |Cite
|
Sign up to set email alerts
|

Protein Sparing Effects of Lipids in The Practical Diets of <i>Oreochromis niloticus</i> (Nile tilapia)

Abstract: A feeding trial was conducted to establish the protein sparing effects of various lipid sources in Oreochromis niloticus fingerlings (mean weight 8.05 ±0.05g) for 8 weeks. Nine experimental diets and one commercial reference diet was used for the trial. The experimental diets comprised of three levels of lipid (L) and protein (P) designated as 15P : 25L, 10P : 30L and 5P : 35L ratios. Three lipid sources used were groundnut oil, palm oil and fish oil. The result obtained showed significant differences (P<0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Among these parameters, only fat content was significantly different between feed treatments with higher fat content in sinking feeds than extruded floating feeds. In several species, the protein sparing effects of lipids had been reported (Orire and Sadiku 2011;Li et al 2012;Hasan and Khan 2013;Yigit et al 2002;Kikuchi et al 2000) with higher levels of lipids in feeds resulting to higher weight gain in fish. This is in contrast with the results of this study which showed that fish fed on lower lipid level extruded floating feeds attained a higher growth rate than fish fed on sinking feed with higher lipid content.…”
Section: Discussionmentioning
confidence: 97%
“…Among these parameters, only fat content was significantly different between feed treatments with higher fat content in sinking feeds than extruded floating feeds. In several species, the protein sparing effects of lipids had been reported (Orire and Sadiku 2011;Li et al 2012;Hasan and Khan 2013;Yigit et al 2002;Kikuchi et al 2000) with higher levels of lipids in feeds resulting to higher weight gain in fish. This is in contrast with the results of this study which showed that fish fed on lower lipid level extruded floating feeds attained a higher growth rate than fish fed on sinking feed with higher lipid content.…”
Section: Discussionmentioning
confidence: 97%
“…This would render the diet unfit for feeding fish. The high level of mortality can be attributed to high level of lipids in the diet which also resulted in loss of appetite and eventual mortality [17,[26][27][28] also reported that, poor utilization of lipid could be attributed to poor feed intake, which prevented the fish from taking enough nutrients to meet the carcass nutrients requirements for the developments of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have researched into inclusion of various oils in the fish diets [14][15][16][17]. However, inclusion of different sources of lipid in appropriate combination in the diet of Clarias gariepinus has not been fully exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan hasil penelitian ini terlihat bahwa fermentasi onggok menggunakan bakteri B. megaterium SS4b mampu mengubah senyawa kompleks menjadi sederhana, yang tercermin dari peningkatan gula sederhana dari 14,36 mg g -1 menjadi 17,07 mg g -1 ; protein terlarut dari 50,96 µg g -1 menjadi 125,18 µg g -1 dan penurunan serat dari 14,83% menjadi 9,42% sehingga mampu meningkatkan kecernaan bahan onggok dari 43,48% menjadi 78,79%. (Orire & Sadiku, 2011). Retensi protein yang tinggi pada akhirnya akan memberikan dampak positif pada peningkatan laju pertumbuhan harian dan efisiensi pakan ikan.…”
Section: Hasil Dan Bahasanunclassified